Performance evaluation and material parameter perspective of eco-friendly highly efficient CsSnGeI3 perovskite solar cell - Raghvendra; Kumar, Rashmi Ranjan; Pandey, Saurabh Kumar (Superlattices and microstructures, 2019)
Lead toxicity and stability are major hurdles in commercialization of the perovskite solar cell. We present the theoretical investigation and analysis of eco-friendly and stable CsSnGeI3 based solar cell. For better understanding of material parameter, various factors affecting the cell performance such as thickness, doping concentration, defect density and doping density of charge transport layer have been rigorously investigated. From simulation results, we observed that the device performance extensively depends on defect density and doping concentration of perovskite absorber layer. We have proposed Cesium Tin–Germanium Tri-iodide (CsSnGeI3) as an efficient light absorber material as compared to lead counterparts. With optimized parameters of proposed architecture, we have achieved 13.29% efficiency. We have also done the comparative analysis of different hole transport layer (HTL) layers to replace spiro-OMeTAD. The results indicate that CsSnGeI3 can be a great prospective to be an absorber layer for high-efficiency perovskite solar cells. [Display omitted]